A formação inicial em serviço : lugar de encontro e de (re) significação do ser-saber-fazer de professores - Ramos, Rosenaide Pereira dos Reis (Universidade Federal de São Carlos, 2011)
This research focuses on teachers training and on the context of policies, practices, and modalities of higher education for in-service primary teachers according to The Law on Brazilian Education Guidelines and Bases (LDB) 9.394/96. The present study was carried out within the context of the performance of professors from Santa Cruz State University (UESC), in the state of Bahia, Brazil, who were also members of the professional team that worked on the process of development, implementation, and follow through of the curriculum development of the Pedagogy Course (2003-2007) of the PROAÇÃO - Program for In-Service Primary Teacher Education - provided for two hundred public school teachers in fourteen cities in the Southern region of the state of Bahia. According to the profile of the participants professional experience and the curricular activities developed, the object of study was defined as the course contributions to the teachers personal and professional dimensions. Based on the following question: How has the education process proposed by the PROAÇÃOUESC Pedagogy Course contributed for the teachers, who became students in the course, to find the (re) signification of the being-knowing-doing triad both personally and professionally? , the goal of this investigation was to indentify, analyze, and explain, from the teachers perspective, how the course, based on the development of the curriculum, has enabled the teachers to achieve personal and professional gains. In order to answer such question, considering the principles of a qualitative research approach and an analytical-descriptive study design based on theoretical and methodological considerations, this research was conducted with the collaboration of fifty former professors who answered a semi-structured questionnaire providing fundamental information to the understanding of some aspects of the course, such as the place for teachers to find the (re) signification of being-knowing-doing. The findings confirm the hypothesis of this study: the process of development and the practice and content of the curriculum of the Pedagogy PROAÇÃO-UESC, enabled the participant teachers to find their personal being and the professional knowing-doing resignifying their personal and professional practices. In addition, the results obtained also indicate the development of an educational process which corresponds to what researchers in education have been advocating in terms of considering the university as a provider of excellence in teacher education in order to, from the perspective of the identity and the personal and professional development, guarantee proper teachers education recognizing and valuing their knowledge, beliefs, culture, and values, and thus making them social agents with reflexive, critical, and innovative training committed to change people, contexts, and places.
Keywords: Professores - formação; Currículos; Estágios supervisionados; Aprendizagem docente; Desenvolvimento profissional; CIENCIAS HUMANAS::EDUCACAO